Tell el-Murra (Northeastern Nile Delta Survey): Research in 2018 and 2022 - Grzegorz Bąk-Pryc; Natalia Małecka-Drozd; Magdalena Kazimierczak; Katarzyna Lajs-Klose; Natalia Puschhaus; Mariusz A. Jucha (Polish Archaeology in the Mediterranean, 2023)
Work in the 2018 and 2022 archaeological seasons at the site of Tell el-Murra, located in the northeastern Nile Delta, continued in two areas: the settlement (Trench T5), and the cemetery (Trench S3). The research yielded valuable information on the appearance and function of the settlement, whose origins date back to the 4th millennium BC. It undoubtedly flourished during the Early Dynastic period and in the beginning of the Old Kingdom. This is evidenced by numerous remains of utility and storage buildings, in which a large number of fragments of ceramic vessels, as well as stone and flint objects for grain processing and breadmaking have been discovered. An integral part of the settlement was the cemetery, where the deceased were buried in simple pits and cavity graves, as well as in more elaborate built-up structures.